Strategi Membangun Brand Image dan Promosi dengan Sosial Media pada UMKM Jawet Sama Arep - Defri Triadi; Cristi Devi Darnita (STKIP PGRI SITUBONDO, 2021)
Technological advances have made most people take advantage of its sophisticated features. One of them is creating a media brand image of MSME products. Research develops social media as a means of branding. The object of this research is MSMEs Jawet Sama Arep in Gohong Village, Pulang Pisau Regency, Central Kalimantan. MSMEs Jawet Sama Arep is a local community group that produces rattan woven. This study uses a research and development approach. Data collection techniques are collected by collecting observations, gathering information, product design, product design validation, design improvements, product testing, and product publication. The study results show that the number of products produced since 2008-2019 has relatively increased and decreased in different years, given the opportunities for the relatively rapid development of digital technology. Business actors at Jawet Sama Arep MSMEs develop promotional designs using social media on Facebook, Instagram, Line, Youtube, Whatsapp, Telegram, Twitter. Research with the development of brand image through social media can help realize the goals of MSMEs as independent businesses. It is concluded that the achievement of brand image in the components of corporate image, user image, and product image by utilizing social media can be achieved well, compared to before using social media. Keywords: brand image, promotion, media social